Một sơ đồ mới nhằm tăng độ sẵn sang trong các hệ cơ sở dữ liệu phân tán - Hải, Nguyễn Nam (Journal of Computer Science and Cybernetics, 2016)
This paper presents a new scheme that enhances the availability of data in the full replicated distributed database systems. This scheme allaws to tolerate a new type of the partition of the network that the old previous schemes in the same type doesn’t allow. In addition, the update is based on a full distributed algorithm, i.e. every update is performed by all workstations, so parallelism of computations is higher than schemes using semi-distributed algorithm. This paper also offers a correctness proof of the scheme.